Combat sports medicine (Springer, 2010)
A significant body of scientific knowledge has been published in sports medicine in the past few decades, but there is huge demand for practical references that address different types of sport. This demand is highest in combat sports which are both highly physical and mentally demanding, and cause challenging issues such as risk of blood borne infections, weight reduction, head injuries, and stress management.